2007
DOI: 10.1152/ajprenal.00479.2005
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin and calciotropic hormones share regulatory pathways in multidrug resistance protein 2-mediated transport

Abstract: Wever KE, Masereeuw R, Miller DS, Hang XM, Flik G. Endothelin and calciotropic hormones share regulatory pathways in multidrug resistance protein 2-mediated transport. Am J Physiol Renal Physiol 292: F38 -F46, 2007. First published August 15, 2006; doi:10.1152/ajprenal.00479.2005.-The kidney of vertebrates plays a key role in excretion of endogenous waste products and xenobiotics. Active secretion in the proximal nephron is at the basis of this excretion, mediated by carrier proteins including multidrug resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…Signaling appeared to be Ca 2+ dependent, because ET release was blocked by the Ca 2+ -channel blocker, nifedipine, and it was activated (in the absence of nephrotoxicants) by elevated medium Ca 2+ . The calciotropic hormones, parathyroid hormone, PTH-related protein, and stanniocalcin, were also found to interfere with ET-regulated Mrp2 activity through PKC and cGMP signaling (58). Conversely, the results also pointed towards Ca 2+ -independent activation of NOS, suggesting involvement of iNOS that could be confirmed in rat studies (51).…”
Section: Endothelin-1 and Calciotropic Hormonesmentioning
confidence: 71%
“…Signaling appeared to be Ca 2+ dependent, because ET release was blocked by the Ca 2+ -channel blocker, nifedipine, and it was activated (in the absence of nephrotoxicants) by elevated medium Ca 2+ . The calciotropic hormones, parathyroid hormone, PTH-related protein, and stanniocalcin, were also found to interfere with ET-regulated Mrp2 activity through PKC and cGMP signaling (58). Conversely, the results also pointed towards Ca 2+ -independent activation of NOS, suggesting involvement of iNOS that could be confirmed in rat studies (51).…”
Section: Endothelin-1 and Calciotropic Hormonesmentioning
confidence: 71%
“…However, any evaluation of urinary cGMP as a substitute for NO bioavailability requires some caution. Since urinary cGMP excretion is likely to depend on the renal function [23,24], the renal dysfunction of cGMP and NO x excretion in urine may result in the increase of circulating NO x levels. Moreover, it has been reported that a creatinine adjustment of urinary biological indicators assayed in spot urine is not a reliable tool for conversion into 24-h urinary excretion [25].…”
Section: Discussionmentioning
confidence: 99%
“…These observations prompted the question whether calcemic factors, such as PTHrP, would interfere with this transport pathway. Indeed, PTHrP interferes with the endothelin regulated Mrp2 med iated transport (Wever et al, 2006). The inhibitory effect of recombinant PTHrP on Mrp2 mediated transport is con centration-dependent, with a maximal inhibition of 40% at 20-60 nmol l_1, a concentration that indicates a para crine action of PTHrP.…”
Section: Mrp2mentioning
confidence: 98%
“…The endothelin-induced inhibition is additive to the PTHrP-induced effect, indicating that the inhibitions proceed at least partly through separate intracellular pathways. Another interesting observation was that the endogenous PTHrP antagonist stanniocalcin (Verbost et al, 1993), which exerts actions via intracellular calcium and PKC pathways, reverses the combined PTHrP/ET inhibition of Mrp2-transport completely (Wever et al, 2006). Clearly, PTHrP has the nephron as target and studies on PTHrP effects on calcium and phosphate handling by fish kidney are warranted.…”
Section: Mrp2mentioning
confidence: 99%